Anatomical changes in leaves of Piper aduncum L. under different irradiances (Revista Brasileira de Plantas Medicinais, 2024)
The aim of the study was to evaluate the effect of different light conditions on the internal structure of Piper aduncum L. leaves. P.aduncum seedlings were grown for 4 months under different light conditions achieved with shading nets (50, 70, and 100% of luminosity) and with photoconversion nets in red (RN) and blue (BN) colors. Two fully expanded leaves located at the third node were collected from five plants per treatment for paradermal and transverse sections. In the paradermal sections, stomatal density, polar and equatorial diameters, the ratio between polar and equatorial diameters, and trichome density on the abaxial and adaxialsurfaces of the epidermis were evaluated. In the transverse sections, the thickness of the adaxial and abaxial epidermis, cuticle of the adaxial surface, palisade and spongy parenchyma, and leaf blade were assessed. The vessel elements parameters were also evaluated and Carlquist vulnerability index were measured. The results show that P. aduncum changes the internal structure of its leaf when grown under different radiation conditions. It presented greater epidermis thickness, greater stomatal density and smaller diameters of vessel elements, anatomical characteristics favorable to its growth under high irradiances.